THE EXPRESSION OF GENES ASSOCIATED WITH OSTEOBLAST DIFFERENTIATION AND THE MAMMALIAN TARGET OF RAPAMYCIN (mTOR) IN THE BLOOD OF PATIENTS WITH OSTEOPOROSIS - E. V. Chetina; K. A. Maslova; N. V. Demin; M. Yu. Krylov; V. A. Myakotkin (Научно-практическая ревматология, 2011)
Objective: to study an association of bone mineral density (BMD) with the expression of genes associated with the proliferation, survival, and differentiation of osteocytes in the peripheral blood of postmenopausal women with osteoporosis (OP). Subjects and methods. Twenty-eight postmenopausal women with OP and 17 age-matched healthy women were examined. BMD was measured by X-ray absorptionmetry. Alkaline phosphatase activity and calcium and phosphorus levels in the blood were determined by conventional methods. RNA was isolated from the peripheral blood and used to estimate the gene expression, by using real-time polymerase chain reaction (RT-PCR). Results. The postmenopausal women with OP were observed to have a significant increase in the expression of ATG1 (serine-threonine kinase that is responsible for the generation of autophagic vacuoles) as compared to the healthy controls, which suggests that autophagy develops in the blood cells of these patients. This was attended by a considerable reduction in the expression of the mTOR (the mammalian target of rapamycin) gene, a regulator of protein synthesis and cell proliferation, and in that of the genes associated with the differentiation of osteoblasts: transforming growth factor β1 (TGF-β1), Runx 2 (Runt-related transcription factor 2) and total alkaline phosphatase (TAP), and the proinflammatory cytokines tumor necrosis factor-α (TNF-α) and interleukin 1β (IL-1β). The expression of mTOR, TGF- β1, Runx2, and IL-1β genes was positively correlated with BMD in individual areas of the hip. On the contrary, that of ATG1 and TAP was correlated negatively with BMD in this area and positively with that in the spine. Although the expression of the genes in question was not correlated with the serum levels of phosphorus and calcium, that of TGF-β1 was positively related to TAP activity in postmenopausal women with OP. Conclusion. In postmenopausal women with OP, bone loss is accompanied by a significant increase in the expression of the autophagy marker ATG1 and by a reduction in that of mTOR, which may be indicative of the inhibition of protein biosynthesis and cell proliferation and the suppression of the expression of the genes associated with the differentiation of osteoblasts and the proinflammatory cytokines TNF- α and IL-1β. The obtained data on gene expression may be used to search for new disease markers tested in peripheral blood.